Coping with the worst of both worlds: Phenotypic adjustments for cold acclimatization benefit northward migration and arrival in the cold in an Arctic‐breeding songbird. (15th April 2021) - Le Pogam, Audrey; O'Connor, Ryan S.; Love, Oliver P.; Petit, Magali; Régimbald, Lyette; Vézina, François
Abstract: Cold acclimatization (phenotypic adjustments to cope with cold conditions) is an imperative requirement for birds living at high latitudes during the cold depths of winter. Despite the significant remodelling of key phenotypic traits and energetic costs associated with elevating cold endurance, winter cold acclimatization can also provide further carryover benefits to subsequent stages in species wintering, migrating and breeding in cold environments (e.g. the Arctic). We tested this beneficial carryover hypothesis using outdoor captive Arctic‐breeding snow buntings Plectrophenax nivalis, a cold specialist known for its impressive wintering thermogenic capabilities. We compared changes in phenotypic traits supporting cold acclimatization—body composition (body, fat, lean mass, pectoral muscle thickness), oxygen carrying capacity (haematocrit), thermogenic capacity and endurance ( M sum, time to M sum ), cold tolerance ( T a at M sum ) and maintenance energy expenditure (BMR)—between the wintering, migratory and arrival/summer stages. Body mass (+31%), fat mass (+226%) and BMR (+13%) increased relative to the winter phenotype, likely to support the added costs of migration—that is the migratory upregulation hypothesis . In contrast, lean mass, pectoral muscle thickness, haematocrit and thermogenic capacity remained high and stable at winter level across stages in support of the thermal carryover hypothesis . The maintenance of these traits likely offers spare capacity for unpredictable cold environments expected during migration and breeding in the Arctic. Our results thus suggest that birds can extend the long‐term advantages of winter phenotypic adjustments through additional benefits to thermogenic capacity during subsequent life‐history stages. These benefits likely make it possible for Arctic‐breeding birds to maximize success across diverse life‐history stages in the face of extreme cold conditions. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. Résumé: L'acclimatation au froid (ajustements phénotypiques requis pour affronter des conditions environnementales froides) est un impératif pour les oiseaux vivant dans les hautes latitudes durant les mois les plus froids de l'hiver. Malgré le remodelage important des principaux paramètres phénotypiques et les coûts énergétiques associés à l'augmentation de l'endurance au froid, l'acclimatation au froid hivernal pourrait apporter des avantages supplémentaires lors des stades d'histoire de vie ultérieurs comme la migration et la reproduction en conditions froides (e.g. l'Arctique). Nous avons testé cette hypothèse d'effets bénéfiques reportés chez des plectrophanes des neiges ( Plectrophenax nivalis ) en captivité. Ce passereau de l'Arctique est un spécialiste du froid connu pour son impressionnante capacité thermogénique durant l'hiver. Nous avons donc comparé les changements des traits phénotypiques favorisant l'acclimatation au froid ‐ composition corporelle (masse corporelle, lipidique et maigre et épaisseur des muscles pectoraux), capacité de transport de l'oxygène (hématocrite), capacité thermogénique et endurance au froid ( M sum, durée jusqu'au M sum ), tolérance au froid ( T a au M sum ) et taux métabolique de base (BMR) – au cours des stades correspondant à l'hiver, la migration printanière et l'arrivée/été. La masse corporelle (+31%), la masse lipidique (+226%) et le BMR (+13%) ont augmenté par rapport au phénotype hivernal, probablement en support à la migration, ce qui est en accord avec l'hypothèse de la régulation positive pour la migration . En revanche, la masse maigre, l'épaisseur des muscles pectoraux, l'hématocrite et la capacité thermogénique sont restés élevés et stables au niveau hivernal, indépendamment du stade d'histoire de vie, ce qui soutient l'hypothèse de la capacité thermogénique reportée . Le maintien de ces traits phénotypiques hivernaux offre certainement une capacité de réserve pour affronter les environnements froids et imprévisibles auxquels peuvent être confrontés ces oiseaux pendant la migration et la reproduction dans l'Arctique. Nos résultats suggèrent donc que les oiseaux peuvent prolonger les avantages à long terme des ajustements phénotypiques hivernaux par des avantages supplémentaires en termes de capacité thermogénique au cours des étapes ultérieures du cycle de vie. Ces avantages permettent probablement aux oiseaux nichant dans l'Arctique de maximiser leur succès à travers les différents stades d'histoire de vie dans des conditions de froid extrême. A free Plain Language Summary can be found within the Supporting Information of this article.